Autophagic stress; A new cellular response to nanoparticles. Could it be a new strategy for inhibition of liver cancer cell invasion and metastasis? - Chalermchai Pilapong (2020)
© 2020 The Royal Society of Chemistry. We herein report a new biological consequence from a unique interaction between nanoparticles of ferric-tannic complexes (Fe-TA NPs) and liver cancer cells (HepG2.2.15). The Fe-TA NPs were found to accumulate into the cells via specific cellular uptake mechanisms and thereafter disturbed cellular autophagy and cellular pH homeostasis, which led the cells to undergo autophagic stress and eventual death. According to biophysical analysis, the cells undergoing autophagic stress were found to lose their capability of attachment, migration, and movement. Similarly, KEGG analysis demonstrated the down-regulation of TGF-beta indicating that the autophagic stress is capable of reducing cancer cell invasion. Therefore, the Fe-TA NPs could be considered beneficial as a new pharmaceutical nanoplatform for liver cancer treatment via induction of autophagic stress.